Association between attention performance and the different dimensions of DSM-5 depression symptoms - Taboada Gjorup, Ana Lucia; Tolentino Júnior, Julio César; van Duinkerken, Eelco; Marques, André Casarsa; do Carmo Filho, Aureo; Joaquim, Alan Marques; Neves, Vithória Vidotti; Schmidt, Sergio Luis (Frontiers in Psychiatry, 2023)
Objective: Depressive symptoms can be assessed with self-reported questionnaires, such as the Patient Health Questionary-9 (PHQ-9). Previous studies have suggested that the PHQ-9 items can be grouped into somatic and non-somatic clusters. However, the classification of the PHQ-9 item "concentration difficulties" into somatic or non-somatic is still controversial. This controversy may be explained by difficulties experienced by subjects in accurately evaluating their attention problems. The primary objective of this study was to determine the correlation between objective attentional performance and the two clusters of depressive symptoms in hospital employees working in stressful conditions.The participants filled out the PHQ-9 to identify their depressive symptoms. Based on the PHQ-9, the somatic or non-somatic symptoms were measured without considering the question about subjective concentration difficulties. Then, a brief version of the Continuous Visual Attention Test (CVAT) was applied to assess four attentional subdomains. The CVAT is a Go/No-go task that measures number of correct responses (focused attention), number of incorrect responses (behavior-inhibition), average reaction time of correct responses (RTalertness), and variability of reaction time (VRT-sustained attention). The entire task lasted 90 seconds. Correlation analyses assessed the relationships between attentional performance and the two dimensions of depressive symptoms.After applying the inclusion/exclusion criteria, 359 individuals were selected. Their age ranged from 20 to 70 years (mean=40.5, SD=10.37), and the majority was female (67.6%). A predominance in somatic depressive symptoms was present in 231 (64%) participants, whereas 59 (16%) showed a predominance of non-somatic symptoms. Sixty-nine participants (20%) did not show any predominance. Higher somatic scores were associated with higher RTs, whereas higher non-somatic scores were related to an increase in the number of incorrect responses.The predominance of the somatic cluster was related to lower alertness, whereas the predominance of non-somatic cluster was associated with impulsivity/hyperactivity. This result may explain the difficulties associated with correctly classifying the item concentration difficulties. A brief attentional task can be used as an auxiliary tool to correctly identify the different dimensions of attention that are associated with different clusters of depressive symptoms.